2006
DOI: 10.1007/s11274-006-9151-3
|View full text |Cite
|
Sign up to set email alerts
|

Yeast populations associated with the artisanal cheese produced in the region of Serra da Canastra, Brazil

Abstract: The aim of this work was to describe the yeast populations present during the manufacturing of Minas cheese of the region of Serra da Canastra, Minas Gerais state, Brazil. Canastra cheese is produced from raw cow's milk at the farmhouse level using artisanal procedures and natural whey cultures as starters. Samples from 10 farms were studied, and they included: raw milk, natural starter, cheese curd before salting and cheese after 5 days of ripening. The most frequent yeasts in whey, curd and cheese were Debar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 24 publications
6
49
0
5
Order By: Relevance
“…D. hansenii forms a monophyletic group with human pathogenic Candida yeast species (with the exception of Candida glabrata, which is more closely related to Saccharomyces cerevisiae) and, indeed, the asexual state of D. hansenii has been described as Candida famata (Nguyen et al, 2009;Suh et al, 2006). Previous studies have reported the presence of D. hansenii in the human gastrointestinal tract, likely due to foodborne strains (Borelli et al, 2006;Cosentino et al, 2001;Desnos-Ollivier et al, 2008;Hallen-Adams et al, 2015;Vasdinyei and Deák, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…D. hansenii forms a monophyletic group with human pathogenic Candida yeast species (with the exception of Candida glabrata, which is more closely related to Saccharomyces cerevisiae) and, indeed, the asexual state of D. hansenii has been described as Candida famata (Nguyen et al, 2009;Suh et al, 2006). Previous studies have reported the presence of D. hansenii in the human gastrointestinal tract, likely due to foodborne strains (Borelli et al, 2006;Cosentino et al, 2001;Desnos-Ollivier et al, 2008;Hallen-Adams et al, 2015;Vasdinyei and Deák, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Yeasts and molds may enter cheese from a variety of sources, including the starter culture, ambient air, brine, processing equipment, and workers [5,34,39]. Many yeasts can contribute to taste, flavor, and appearance; however, not all species produce beneficial effects, and a species may benefit one cheese while spoiling another.…”
Section: Introductionmentioning
confidence: 99%
“…Canastra cheese is the original name of a variety of Minas cheese produced from raw cow milk in Serra da Canastra, a region located in the southeast of Minas Gerais State (Borelli et al, 2006a). It is a semi-hard cheese that is made at the farm house level using traditional procedures for the last 200 years.…”
Section: Introductionmentioning
confidence: 99%
“…The region produces about 375.5 tons of cheese per month. The milk is coagulated by employing natural whey cultures as starters (which contain indigenous lactic acid bacteria) and commercial rennet, and ripening occurs via the natural microbiota present in the milk and in the environment (Borelli et al, 2006a). After being manufactured, Canastra cheese presents a pale cream color that becomes yellow during the ripening process.…”
Section: Introductionmentioning
confidence: 99%